EKONOMI DIGITAL, UMKM, DAN TRANSFORMASI PASAR KERJA: STUDI KONTEKSTUAL DI INDONESIA - Martha Octavia Dwi Sisianty (Adisam Publisher, 2026)
This study aims to analyze the role of the digital economy in the growth of Micro, Small, and Medium Enterprises (MSMEs) and the transformation of labor market structures in Indonesia. The rapid development of digital technology has significantly changed economic activities, business models, and employment patterns in modern society. MSMEs, as the backbone of the Indonesian economy, are increasingly integrated into the digital ecosystem through e-commerce, fintech, digital marketing, and online platforms. However, the acceleration of digital transformation also creates challenges related to digital inequality, workforce adaptation, and skills mismatch in the labor market. This research employs a qualitative approach using the library research method, examining scientific literature, Scopus-indexed journals, books, policy documents, and relevant reports on the digital economy, MSMEs, and employment transformation. The findings indicate that the digital economy positively contributes to MSME productivity, market expansion, business innovation, and economic competitiveness. Furthermore, digital transformation encourages the emergence of new technology-based occupations and more flexible work patterns. Nevertheless, the study also reveals that limited digital literacy, unequal technological infrastructure, and low workforce readiness remain major obstacles in maximizing the benefits of the digital economy. Therefore, inclusive policies that focus on improving digital literacy, developing workforce skills, expanding infrastructure, and enabling sustainable MSME digitalization are essential to ensure equitable and sustainable economic growth in Indonesia.